Cover Feature: Hybridization of Palladium Nanoparticles with Aromatic‐Rich SU‐101 Metal‐Organic Framework for Effective Transfer Hydrogenation (Eur. J. Inorg. Chem. 25/2022). Issue 25 (27th July 2022) - Krishnaveni, Valle; Esclance DMello, Marilyn; Basavaiah, Keloth; Samsonu, Dasi; Rambhia, Dheer A.; Kalidindi, Suresh Babu
Abstract : The Cover Feature shows utilization of a π‐electron rich metal‐organic framework (SU‐101) for the stabilization of Pd nanoparticles and its application for the reduction of 4‐nitrophenol (4‐NP) to 4‐aminophenol (4‐AP) via transfer hydrogenation in the presence of ammonia borane. SU‐101 is a polyphenolate‐based MOF that is constructed with Bi(III) metal ion and ellagic acid organic linker. Ellagic acid is an antioxidant and can be obtained from natural sources like grapes, strawberries, walnuts, and pomegranates. SU‐101 has a π‐electron rich, rod‐like structure with continuous conjugation. The aromatically rich ellagic acid helps the SU‐101 MOF to draw organic aromatic molecules such as 4‐NP into its pore channels. Pd nanoparticles were effectively stabilized over SU‐101 using the wet‐impregnation method. Owing to the presence of a π electron rich environment around Pd nanoparticles, Pd/SU‐101 exhibited excellent catalytic activity. Over Pd/SU‐101, 4‐NP has been transferred into 4‐AP within 10 min at room temperature (turn over frequency=2421 h −1 ) using ammonia‐borane under optimized conditions. Kinetics studies have shown that the reaction proceeds through a Langmuir–Hinshelwood mechanism. More information can be found in the Research Article by S. B. Kalidindi and co‐workers .